SOURCES OF ENRICHMENT OF THE VOCABULARY OF THE UZBEK AND KORAKALPOK LANGUAGES - Boboyev Yusuf Beknazarovich (Journals Park Publishing, 2023)
The article talks about the enrichment and sources of the lexicon of the Uzbek and Karakalpak languages.
Keywords: language units, linguists, terminology, Karakalpak language, lexicon.